ENGINEERING EDUCATION: PRACTICE-ORIENTED APPROACH - N. N. Dvulichanskaya; V. B. Piasetsky (Высшее образование в России)
The paper substantiates the need to strengthen the practical orientation of engineering education in modern socio-economic conditions. The paper shows that introduction of context-related tasks during classroom hours correspond to the implementation of practice-oriented approach. The paper gives the examples of applied tasks in training of engineers that illustrate how general educational and general technical disciplines are associated with the features ofprofessional activity of a future optoelectronics engineer. The authors mark out the competences of technical students that may be formed in the process ofsolving contextual tasks with interdisciplinary content. It is noted that the reflection in the task content the real life situations relating to the future profession increases students' motivation to learn and acquire competencies.